Staphylococcus hominis subspecies can be identified by SDS-PAGE or MALDI-TOF MS profiles - Pereira, Eliezer Menezes (Sci Rep, 2019)
Staphylococcus hominis is part of the normal human microbiome. Two subspecies, S. hominis hominis (Shh) and S. hominis novobiosepticus (Shn), have clinical significance. Forty-nine S. hominis isolates were analyzed by the MicroScan automated system, SDS-PAGE and MALDI-TOF methods, followed by partial sequencing of the 16S rDNA gene. The trehalose fermentation test, disk diffusion and broth microdilution tests were used to identify (novobiocin test) and access the susceptibility to oxacillin and vancomycin of isolates. The SCCmec elements and genomic diversity were evaluated by PCR and PFGE methods, respectively. Profiles of 28 (57%; 8 Shh and 20 Shn) isolates corroborated with the results found in all the applied methods of identification. The remaining 21 (43%) isolates were phenotypically identified as Shh by MicroScan; however, they were identified as Shn by SDS-PAGE and mass spectral, and confirmed by 16S rDNA sequencing. Among 41 isolates identified as Shn by the molecular and mass spectrometry methods, 19 (41%) were novobiocin-sensitive, and the trehalose test indicated 11 positive isolates, which are considered atypical phenotypic results for this subspecies. In addition, 92.7% of the isolates identified as Shn by these methods carried mecA gene, while only 12.5% of the Shh isolates were positive. Together, the results highlighted the SDS-PAGE and MALDI-TOF MS methods as promising tools for discriminating S. hominis subspecies.